Etika Bisnis Islam dalam Transaksi Keuangan Menggunakan Aplikasi Mobile Banking/M-Banking - Tito Nur Mustika (Program Studi Ekonomi Syariah dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2023)
Technology is developing very rapidly so that it encourages Muslims to also adapt to the latest technology. One of them is non-cash or cashless payment financial transactions. Mobile-Banking is a service that makes it easier for customers or users to make non-cash transactions via smartphones. With services that can be accessed 24 hours and supported by an internet network, customers get convenience and comfort in financial transactions anywhere and anytime by using M-Banking application. In this way, Muslims are expected to be able to avoid debt or delay paying in a transaction and remain in Islamic business ethics. So, in carrying out its business, customers dosen’t need to worry. The Ijarah principle is the principle used by M-Banking application. Thus, banks may charge service fees/fees/Ujrah to account owners for the use of M-Banking services. In terms of transactions, M-Banking may be used for business transactions in which both the substances and systems and procedures for obtaining profits are not prohibited by Islamic teachings.